Hone Tuwhare: At the Interface of Poetic Traditions - Collett, University of Wollongong, Australia, Anne (Asiatic: IIUM Journal of English Language and Literature, 2012)
Hone Tuwhare was a poet of wide popular appeal and generally beloved of New Zealanders, Maori and Pakeha alike. His poetry combined Maori and English poetic traditions, and gave voice to many of the popular protest moments of the 20th century. Yet his poetry is no longer available in bookshops and most volumes of his poetry are out of print. The essay examines this apparent anomaly, and considers the impact of the rise and fall of print culture on oral poetic traditions.